Implementation of Digital Marketing Communication in Increasing Pilgrims' Interest in Zafa Tour Hajj & Umrah Service Bureau - R.M. Faiz Alhaqi; Yenrizal; Badarudin Azarkasyi (Universitas Muhammadiyah Palu, 2026)
This research was conducted to examine in depth the implementation of digital marketing communication carried out by Zafa Tour and analyze various development opportunities in increasing the interest of prospective pilgrims. This research aims to understand how digital marketing communication is applied through the stages of Attention, Interest, Desire, and Action (AIDA) in forming interest to the decision to register prospective pilgrims. This study uses a descriptive qualitative method with data collection techniques through in-depth interviews with marketing leaders and staff. The results of the research on the implementation of digital marketing communication in increasing the interest of prospective pilgrims in the Zafa Tour Hajj and Umrah service bureau, it can be concluded that the digital marketing communication strategy implemented has been effective and in accordance with the stages of AIDA theory.